Turismo de aventura en la provincia de El Oro. - Moreno Montero, Angie Gabriela; Paladines Fernandez, Patricia Mirella (My University, 2021)
The province of El Oro has a unique diversity of flora and fauna, its natural charm captivates everyone who visits it. Its tourist attractions are ideal to practice recreational and fun adventure tourism; this type of tourism goes beyond just generating an economic profit; but rather it becomes a means of tourism education for those who practice it. The main purpose of this research work is to design a tourist route aimed at children between 8 and 12 years of age, within the cantons of El Guabo, Pasaje and Santa Rosa in the province of El Oro, Ecuador. A non-experimental methodology was used, with a qualitative and quantitative approach; and a transversal temporality, the survey and observation were used as instruments: hierarchy cards. The insitu visits were carried out over a period of approximately one month, during which time sufficient information was obtained to fill out the ranking cards for the selected natural attractions. The stakeholders involved in the study were the parents of the three cantons. The results show a tourist route that satisfies the needs of the demand, where the attractions and adventure activities maintain safe conditions for their development. A route is established to educate children and involve them in tourism, so that in the future they will be interested in promoting the tourist attractions of their province.
La Provincia de El Oro tiene una diversidad de flora y fauna única, su encanto natural logra cautivar a todo el que la visite. Sus atractivos turísticos son ideales para practicar un turismo de aventura recreativo; este tipo de turismo va más allá de solo generar un lucro económico; sino más bien se convierte en un medio de educación turística para quien lo practique. El turismo de aventura alternativa El presente trabajo de investigación tiene como objetivo principal diseñar una ruta turística dirigida a niños y niñas entre los 8 a 12 años de edad, dentro de los cantones El Guabo, Pasaje y Santa Rosa de la Provincia de El Oro, Ecuador. Se ha empleado una metodología no experimental, con un enfoque cualitativo y cuantitativo; y una temporalidad transversal, se utilizó como instrumentos la encuesta y la observación: fichas de jerarquización. Las visitas insitu se realizaron en un período de tiempo de aproximadamente un mes; es este lapso se logró obtener suficiente información para llenar las fichas de jerarquización de los atractivos naturales seleccionados. El actor involucrado para el estudio fue la población de padres de familia de los tres cantones. Dentro de los resultados se muestra una ruta turística que satisface las necesidades de la demanda, donde los atractivos y las actividades de aventura mantienen condiciones seguras para su desarrollo. Se establece un recorrido donde se trata de educar a los menores e involucrarlos en el ámbito turístico; para que en un futuro tengan interés por potenciar los atractivos turísticos de su provincia.
Keywords: ACTIVIDADES TURÍSTICAS; ATRACTIVOS NATURALES; DISEÑO DE RUTAS TURÍSTICAS; TURISMO DE AVENTURA